Insights into equine hepacivirus: assay development and transmission patterns - Radley, Mirelle (2024)
Equine hepacivirus A (EqHV) is most genetically similar to hepatitis C and causes liver disease in horses. EqHV has been detected in equids globally since 2011, but several aspects about the virus are yet to be established, including transmission and clinical impact.